Influence of UAV flight speed on droplet deposition characteristics with the application of infrared thermal imaging - Lv, Meiqiao; Xiao, Shupei; Yu, Tang; He, Yong (International Journal of Agricultural and Biological Engineering, 2019)
A plant protection unmanned aerial vehicle (UAV) applied for spraying pesticide has the advantages of low cost, high efficiency and environmental protection. However, the complex and changeable farmland environment is not conductive to perform spray test effectively. It is therefore necessary to carry out spray test under controlled conditions. The current study aimed to illuminate the variation law of droplet deposition characteristics under different UAV flight speeds, and to verify the feasibility for applying infrared thermal imaging in detection of droplet deposition effects. A UAV simulation platform with an airborne spray system was established and an analysis program Droplet Analysis for dealing with water-sensitive paper was developed. The results showed that, when the flight speed was set at 0.3 m/s, 0.5 m/s, 0.7 m/s, 0.9 m/s and 1 m/s, respectively, the droplet deposition density, droplet deposition coverage and arithmetic mean of droplet size D0 decreased as the UAV flight speed increased. On the contrary, the droplet diameter variation coefficient CV increased with the increase of UAV flight speed, resulting in the worse uniformity of sprayed droplet distribution as well. The results can provide a theoretical support for optimizing the spraying parameters of plant protection UAV, and demonstrate the practicability of infrared thermal imaging in evaluating the droplet deposition in the field of aerial spraying.Keywords: spray test, UAV flight speed, droplet deposition characteristics, droplet analysis, image processing, infrared thermal imagingDOI: 10.25165/j.ijabe.20191203.4868Citation: Lv M Q, Xiao S P, Tang Y, He Y. Influence of UAV flight speed on droplet deposition characteristics with the application of infrared thermal imaging. Int J Agric & Biol Eng, 2019; 12(3): 10–17.